Microcomputer-based instruction for end users: Experimental trials of the OAK interface for DOE/RECON - Case, Donald Owen; Borgman, Christine L.; Meadow, Charles T. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
see attached